The Effect of Workload and Job burnout on Turnover Intention with Job satisfaction as mediation variable (Study at PT.Indiratex Spindo) - Yupono Bagyo; Darrel Rafif Zulfikar (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
This study aims to analyze the effect of workload and job burnout on turnover intention, with job satisfaction as a mediating variable at PT Indiratex Spindo. A quantitative approach was applied using Partial Least Square (PLS) analysis. The sample consisted of 60 employees selected through the Slovin formula. Data collection was conducted using a questionnaire with a Likert scale. The results indicate that workload does not significantly affect turnover intention but has a significant positive effect on job satisfaction. Job burnout negatively and significantly affects job satisfaction but does not significantly impact turnover intention. Job satisfaction has a negative and significant influence on turnover intention. Furthermore, job satisfaction mediates the effect of workload and job burnout on turnover intention. These findings provide insights for companies in managing workload and job burnout to improve job satisfaction and reduce turnover intention